PENERAPAN GENIUS LOCI PADA PEMUKIMAN MASYARAKAT NGADAS TENGGER MALANG - Hammam Rofiqi Agustapraja (Litbang Pemas - Universitas Islam Lamongan, 2017)
Settlement is a human living environment that has distinctive characteristics and serves as a place, space, and container for the growth and development of human culture as part of the residential community. If in a permukinman community has undergone changes, growth and development, it will certainly have an impact on the human being that is part of the community. The elements of settlement include the spatial pattern formed on the micro scale to the macro scale (village) is strongly influenced socio-cultural factors of society.